2011
DOI: 10.1002/mus.21933
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis and protein processing in late‐onset pompe disease patients with low levels of acid α‐glucosidase activity

Abstract: There is no common mutation associated with <1% GAA activity in late-onset Pompe disease patients. Most patients produce unprocessed forms of GAA protein compared with patients with higher GAA activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…We screened our database and found that 4 of the 106 adults in our patient cohort have a Molecular Genetics and Metabolism 107 (2012) 485-489 low GAA activity in fibroblasts within the range of classic-infantile patients. None of these four patients have the common c.-32-13 T > G mutation but other pathogenic mutations, as described previously [12][13][14][15]. We described one of the patients earlier [16].…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…We screened our database and found that 4 of the 106 adults in our patient cohort have a Molecular Genetics and Metabolism 107 (2012) 485-489 low GAA activity in fibroblasts within the range of classic-infantile patients. None of these four patients have the common c.-32-13 T > G mutation but other pathogenic mutations, as described previously [12][13][14][15]. We described one of the patients earlier [16].…”
Section: Introductionsupporting
confidence: 54%
“…It is notable that none of the adult patients with unexpected low activity in fibroblasts, including the thirteen cases recently reported by Bali et al [12], carry the most common mutation c.-32-13 T > G which is frequently associated with a later onset and slowly progressive phenotype [13][14][15][16]. It is also remarkable that in all these exceptional cases, close to normal synthesis of the 110 kDa precursor form can be demonstrated in the fibroblasts by immunoblotting, but that processed forms of 95 kDa and 76 kDa are virtually lacking.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Kroos et al [38] reported that the presence of at least one mutation allows the production of a protein with some residual activity that leads to the late-onset forms. However, another study showed that no common mutation is associated with b1%GAA activity in LOPD patients [39]. The documented clinical variability in patients with similar genotypes [36] still makes genotype-phenotype correlation an unresolved issue.…”
Section: Discussionmentioning
confidence: 99%
“…All of them had the most common leaky splice variant c.-32-13T>G as second mutation [23]. W746* has also been reported in heteroallelic combination with the less severe P285S variant and was in that case associated with late-onset disease [24]. The fact that W746* was rather frequently seen in humans and is now also found in dogs suggests that the chromosomal region around c.2237G is a mutation hotspot.…”
Section: Discussionmentioning
confidence: 98%